Settlement of strip footing on sandy soil due to eccentricity - Braim, Krekar Saber (2015)
The failure behaviour of the shallow foundation under centric and eccentric loading has been studied extensively. Bearing capacity and settlement are two limits of foundation design. The studies on the effect of eccentricity on bearing capacity are abundant, while the study about the effect of eccentricity on settlement is very rare. The aim of this study is to investigate the effect of eccentricity on settlement of sandy soil. The objectives of this research involve the evaluating the ultimate and allowable bearing capacity and verifying bearing capacity factor (Ny), determination of settlement of sandy soil under different eccentricity ratio (e/B), analysing the failure mechanism of strip footing on cohesionless soil by close range photogrammetry and particle image velocimetry (PIV) methods, and verifying the laboratory results with theory or analytical analysis for centrally loaded strip footing. This research mainly concentrates on the laboratory tests. Several tests were conducted which consist of physical property tests and small scale physical modelling test. A model of medium sand with 50% relative density was prepared, strip footing was replicated using a rigid plate and loaded with different eccentricity. Moreover, close range photogrammetry and PIV technique were used to observe the failure pattern, contour of displacement, and shear strain under strip footing. It was found that the settlement increases with increasing eccentricity.